2004
DOI: 10.1111/j.1365-2893.2004.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum immunoglobulins predict the extent of hepatic fibrosis in patients with chronic hepatitis C virus infection

Abstract: Recently, we documented that immunoglobulins stimulate the proliferative activity of rat hepatic stellate cells in vitro. The aim of the present study was to determine whether there is any association between serum immunoglobulin levels and hepatic fibrosis in patients with chronic hepatitis C virus (HCV) infection. Charts from 116 patients with biochemical, serologic, virologic and histologic evidence of chronic hepatitis C infection and serum immunoglobulin levels (IgA, IgG, IgM and total) were reviewed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
33
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 25 publications
10
33
0
2
Order By: Relevance
“…Maruyama et al (21), reported a correlation between serum IgG levels and the severity of the disease in 102 patients with cHepC and significant decrease in levels by treatment. Gonzàlez-Quintela et al and Watt et al also described significantly higher levels of IgG and IgA in patients with cHepC (22,23). Our results further confirm these studies: significantly higher immunoglobulin levels in cHepC patients compared to controls and correlation of IgG with HAI and FS in non-uremic patients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Maruyama et al (21), reported a correlation between serum IgG levels and the severity of the disease in 102 patients with cHepC and significant decrease in levels by treatment. Gonzàlez-Quintela et al and Watt et al also described significantly higher levels of IgG and IgA in patients with cHepC (22,23). Our results further confirm these studies: significantly higher immunoglobulin levels in cHepC patients compared to controls and correlation of IgG with HAI and FS in non-uremic patients.…”
Section: Discussionsupporting
confidence: 82%
“…High IgG levels in cHepC patients have been shown to affect prognosis and response to therapy (21)(22)(23)(24). Maruyama et al (21), reported a correlation between serum IgG levels and the severity of the disease in 102 patients with cHepC and significant decrease in levels by treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde, fibrozisle giden kronik karaciğer hastalıklarında, Kupfer hücrelerinin portal venöz sisteme dağılan antijenleri temizleme kapasitesinin azaldığı, bu nedenle sirkulasyona daha fazla antijen geçtiği ve bunun sonucu olarak da immünoglo-bulin sentezinin arttığı bildirilmektedir. 28 Biz de çalışmamızda, ağır fibrozisi olan hastalarda IgA dü-zeylerini hafif-orta fibrozisi olan hastalardan daha yüksek bulduk. Fibrozisle orantılı olarak artan immünoglobulinler, daha fazla çalışmayla desteklendiğinde, gelecekte fibrozis derecesini belirlemekte kullanılabilir.…”
Section: Discussionunclassified
“…A strong association was found between serum immunoglobulin levels and hepatic fibrosis, particularly in patients with chronic hepatitis B virus and hepatitis C virus infection and auto-immune hepatitis (Watt et al 2004, Schmilovitz-Weiss et al 2006, Lüth et al 2008. Silveira et al (2002) reported significantly higher IgG4 levels in patients with PPF when evaluating IgG4 in schistosomotic patients with and without PPF.…”
Section: Serum Type VI Collagenmentioning
confidence: 97%